Context-Aware Service Selection with Uncertain Context Information - Vanrompay, Yves; Kirsch-Pinheiro, Manuele; Berbers, Yolande (Electronic Communications of the EASST, 2009)
The current evolution of Service-Oriented Computing in ubiquitous systemsis leading to the development of context-aware services. These are serviceswhose description is enriched with context information related to the service executionenvironment and adaptation capabilities. This information is often used for discoveryand adaptation purposes. However, in real-life systems context informationis naturally dynamic, uncertain and incomplete, which represents an important issuewhen comparing service description and user requirements. Uncertainty of contextinformation may lead to an inexact match between provided and required servicecapabilities, and consequently to the non-selection of services. In order to handleuncertain and incomplete context information, we propose a mechanism inspiredby graph-comparison for matching contextual service descriptions using similaritymeasures that allow inexact matching. Service description and requirements arecompared using two kinds of similarity measures: local measures, which compareindividually required and provided properties, and global measures, which take intoaccount the context description as a whole. We show how the proposed mechanismis integrated in MUSIC, an existing adaptation middleware, and how it enables moreoptimal adaptation decision making.